2002
DOI: 10.1021/jp021881u
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of the Brønsted-Acid Catalysis ofn-Hexane → Propane + Propene, Featuring Carbonium Ions

Abstract: A hypothetical five-step catalytic cycle for Brønsted-mediated fission of an all-trans n-alkane was examined using density functional theory. Optimized geometries and transition states were determined for catalystreactant complexes, using three different monodentate catalyst ions (NH 4 + , H 3 O + , and H 2 F + ). Despite the wide variety of catalyst acidities, protonated hexane appears as an intermediate (not a transition state) in each case. The protonated cyclopropane structure is the most likely initial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…12 (AlHCl 3 G catalyst), the biggest difference relative to Fig. 11 is that the energies of the ion-pair intermediates (the lower half of the plot) have dropped significantly nism meshes nicely with our earlier study on the protolysis of hexane (23), which demonstrated that catalyst acidity could cause qualitative differences in its mechanism.…”
Section: Visualizing and Comparing The Two Catalyst Mechanismssupporting
confidence: 78%
See 1 more Smart Citation
“…12 (AlHCl 3 G catalyst), the biggest difference relative to Fig. 11 is that the energies of the ion-pair intermediates (the lower half of the plot) have dropped significantly nism meshes nicely with our earlier study on the protolysis of hexane (23), which demonstrated that catalyst acidity could cause qualitative differences in its mechanism.…”
Section: Visualizing and Comparing The Two Catalyst Mechanismssupporting
confidence: 78%
“…For example, the effect of the relative acidity or basicity of the catalyst upon the mechanism can be studied, without the need to invoke large-scale modelling. In 2003, our group published a theoretical study on an idealized Bronsted acid catalytic cycle for C 6 H 14 → C 3 H 8 + C 3 H 6 , using small cationic Bronsted acids in the computations (23). There we demonstrated that the existence of certain intermediates varied with the catalyst, simply because of the acidity of the catalyst.…”
Section: Introductionmentioning
confidence: 94%
“…Note also that ten of the 11 low-energy longarm-clinal forms are also closed forms, thus demonstrating a general prevalence for closed forms on the PES in agreement with past studies. [9][10][11][12][13][14][15][16][17][18][19][20] Curiously, the lowest-energy form, with two clinal longarms, is not fully closed but open-clinal on both sides.…”
Section: A Optimized Pw91/ 6-31g"d P… Structuresmentioning
confidence: 99%
“…For instance, he performed restricted optimizations of the structures of several small alkyl ions in ion-pair complexes with the approaching and weakly nucleophilic H 3 BF − ion 13,14,41,42 and found that open structures become lower in energy than closed ones on the PES once the anion approaches within ϳ3 Å of the cation. In contrast, one of us has done unrestricted optimizations of complexes of closedstructure alkyl ions with NH 3 , 17 H 2 O, 17 20 and various small zeolite fragment ions, 19,20 and no structure-opening was seen unless the alkyl ion became covalently bonded to the nucleophile. We see open secondary ions, without ion-pairing, in our simulations of alkyl ions in zeolites or ionic liquids at catalytic temperatures.…”
Section: Other Effects On Open Versus Closed Structuresmentioning
confidence: 99%
See 1 more Smart Citation